Effect of Fun Teaching Methods Using Flash Card on Motivation and Learning Mathematics - Iis Aisah (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2016)
Teachers as a source of learning is obliged to provide a creative learning environment for students learning activities in the classroom. One of the teachers should do is pick and choose methods and media that will be used in learning activities. Less precise in selecting methods and learning media can be fatal to the students so that the students' motivation to learn mathematics to be low. Learning is packed with mood full of joy can motivate students to learn mathematics. The process of learning by playing eliminating pressures and boredom that learning activities can be run well. Fun bembelajaran teaching is a method that can make a pleasant atmosphere so that learning and teaching did not become monotonous and boring. Instructional media Flash cards is the right medium to help students / children remember and learn new information. In its implementation, the method fun teaching using instructional media flash card not only degan play or storytelling but the method fun teaching using instructional media flash card to make students become more creative, and the atmosphere of intimacy between students and teachers more closely so that the study of mathematics was not be a scary lesson for students. This study aimed to see whether fun method of teaching using instructional media flash card can affect motivation for mathematics students. And to know the students' motivation to learn math using Fun Teaching and learning media Flash Card. The research method used was experimental research design pretest-posttest control group design. The population in this study were all students in class VIII SMP Sindangjawa Academic Year 2013/2014 comprising four classes totaling 141 students. While the sampling technique used was simple random sampling technique by means raffle. The sample in this study was VIIIB class numbering 36 students as an experimental class and class VIIIC the 36 students as the control class. This study used questionnaires. Before analyzing the data, performed first prerequisite test analysis is the normality test and homogeneity test. Then proceed with the regression, coefficient of determination and significance test / t-test to look for the influence fun method of teaching using instructional media flash card on motivation to learn math students. Based on the results of the study, showed that the fun method of teaching using instructional media in learning math flash cards received good response. Motivation to learn mathematics students increased by 17.306. Data analysis techniques used in this study is a t-test, and based on the t-test is obtained t_hitung t_tabel = 6.151 and 1.697. Based on the significant value of 5%, which means t_hitung> t_tabel, thus H_0 H_a rejected and accepted. So it can be concluded that there are significant fun method of teaching using instructional media flash card on motivation to learn math students.